Semantic agent architecture: embedding ontology into the agent's reasoning engine - Chin, Kim On; Gan, Kim Soon (Universiti Malaysia Sabah, 2014)
This research presents the development of semantic agent architecture which incorporates semantic technology that allows decision making, reasoning and learning. The agent architecture is the software architecture that is intended to support decision making process for intelligent agent. From the review of existing agent architectures, BDI architecture is chosen to incorporate semantic technology due to the widely adoption of BDI architecture. The BDI architecture is based on the practical reasoning and mentalistic notion. Semantic technology is set of technologies that make data more easily machine-processable. Thus, by incorporating semantic technology into BDI architecture, a semantic agent architecture that allows decision making, reasoning and learning is created. This study illustrates the semantic agent architecture through simple trading system. The trust and reputation are augmented into the agent architecture to allow the agent to evaluate the performance of the other agent.